2011
DOI: 10.1002/dvdy.22762
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Id2 in the second heart field and cardiac defects in Id2 knock‐out mice

Abstract: The inhibitor of differentiation Id2 is expressed in mesoderm of the second heart field, which contributes myocardial and mesenchymal cells to the primary heart tube. The role of Id2 in cardiac development is insufficiently known. Heart development was studied in sequential developmental stages in Id2 wildtype and knockout mouse embryos. Expression patterns of Id2, MLC-2a, Nkx2.5, HCN4, and WT-1 were analyzed. Id2 is expressed in myocardial progenitor cells at the inflow and outflow tract, in the endocardial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 174 publications
(359 reference statements)
0
19
0
Order By: Relevance
“…It has been shown that Id2 is prominently expressed in the ventricular conduction system, including the atrioventricular bundle and the bundle branches, and is required for the development of the ventricular conduction system (Moskowitz et al, 2007). However, Id2 is largely absent in atrial myocardium (Jongbloed et al, 2011; Moskowitz et al, 2007). Our ChIP-seq and qRTPCR results suggest a direct repression role of COUP-TFII on the expression of Id2 (Figure 6F).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Id2 is prominently expressed in the ventricular conduction system, including the atrioventricular bundle and the bundle branches, and is required for the development of the ventricular conduction system (Moskowitz et al, 2007). However, Id2 is largely absent in atrial myocardium (Jongbloed et al, 2011; Moskowitz et al, 2007). Our ChIP-seq and qRTPCR results suggest a direct repression role of COUP-TFII on the expression of Id2 (Figure 6F).…”
Section: Discussionmentioning
confidence: 99%
“…Knock out mouse models evaluating Id genes have demonstrated their essential role in development. Id2 null mice displays phenotypic abnormalities of retarded growth and neonatal morbidity due to a lactation defect [4], impaired chondrogenesis [5], B cell development [6] and severe cardiac defects [7]. Male Id2-/- mice also exhibit defects in spermatogenesis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Id2 participates in various processes during the heart development, including myogenesis, neurogenesis, cell growth and cell differentiation [13][14][15]. Removal of Id2 from the cardiac neural crest results in structural defects in the outflow tract (such as the common arterial trunk), and a significant loss would be observed in the Id2 expression in the outflow tract.…”
Section: Correlation Analysis Between Id2 Gene Methylation Level and mentioning
confidence: 99%